Fibroblast growth factor 21 enhances angiogenesis and wound healing of human brain microvascular endothelial cells by activating PPARγ - Wenting Huang; Mingjie Shao; Huan Liu; Jun Chen; Jian Hu; Liyun Zhu; Fei Liu; Dongxue Wang; Yuchi Zou; Ye Xiong; Xue Wang (Elsevier, 2019)
Angiogenesis of brain microvascular endothelial cells (BMECs) is required in the functional restoration of brain injury, such as traumatic brain injury (TBI) and ischemic stroke. Fibroblast growth factor 21 (FGF21) is an angiogenic molecule that functions through the formation of the FGF21/FGFR1/β-klotho complex but does not cause carcinogenic events. The current study was to determine whether recombinant human FGF21 (rhFGF21) could promote angiogenesis and scratch wound healing of human brain microvascular endothelial cells (HBMECs) and the possible underlying mechanism. rhFGF21 promoted angiogenesis and migration of HBMECs. The FGFR1 inhibitor PD173074 was applied to demonstrate that rhFGF21 functions through the formation of FGF21/FGFR1/β-klotho complexes. In addition, the specific PPARγ inhibitor GW9662 and PPARγ activator rosiglitazone were applied to determine that the role of rhFGF21 in increasing angiogenesis is through the PPARγ pathway. In addition, we revealed that the effect of rhFGF21 acts partially through upregulating eNOS expression. In conclusion, our study provides novel evidence that rhFGF21 can enhance the angiogenesis and migration of HBMECs through the formation of the FGF21/FGFR1/β-klotho complex via PPARγ activation and eNOS upregulation, indicating that FGF21 is a potential therapeutic angiogenic agent for the treatment of human brain injury. Keywords: Angiogenesis, Wound healing, FGF21, FGF21/FGFR1/β-klotho complex, PPARγ